Not he or she, I'm me - Wild, A. M. (Henry Holt and Company, 2023)
A child gets ready for a wonderful day. They gleefully get dressed, hug their parents, go to school, and play with friends. All the while, unapologetically reminding themselves that they are and can only be themselves. The nonbinary experience is brightly illustrated as we follow our main character through their typical day. The story's bouncy and fun refrain reminds all readers of gender-neutral pronouns and affirms the identities of nonbinary children - encouraging readers to practice empathy for themselves and others.